Liraglutide Drug Loading with Double Layered Hydroxide- Synthesis and Characterization - Sevan Adeeb Doshan; Mustafa Ghazi Alabassi; Ashuor Hamood Dawood (College of Pharmacy / Mustansiriyah University, 2020)
The liraglutide, antidiabetic drug, was loaded with layered double hydroxide nanoparticles  for selective ions such as Fe+3, Fe+2, Ni+2 and Al+3, the LDH were prepared through the titration method by adding 2M of NaOH to the mixture of trivalent, divalent ions and 0.5M HCl, the   drug   liraglutide   was   added    to Prepared layered. The compounds were characterized by SEM, AFM, FT-IR, XRD and Zeta potential technique.